Effects of project-based learning strategy on Iranian educational technology students' self-directed learning readiness, technology competency, and learning performance - Bagheri, Mohsen (2013)
This study sought to examille the effects of project-based learnillg strategy (PoBL) on self-directed learning readiness, technology competellcy, alld leat'nillg performance amollg Educatiollal Technology nlldergraduate students of Iran. In order to achieve this objective, a sample of 78 students who enrolled in the System-Based Education course were randomly assigned to experimelltal group (PoBL strategy) alld cOlltrol group (conventiollal teaching strategy). As the research instrumentation , a self-directed learning readilless scale, techllology competency questionnaire, alld System-Based Education achievement test were administrated at three phases namely, pre-test, mid-test, and post-test. Data analysis consisted of descriptive statistics alld inferelltial statistics. The descriptive results showed that: 1) studellts in experimelltal group achieved higher meall scores thall cOlltrol group in terms of overall self-directed learnillg readiness (M e,01'=169.2 vs Meont= 153.4), and its componellts such as self-management (M exp=51.60 vs Meont=45.95), desire for leaming (Mexp=56 .26 vs Mmnt=51.82) and self-control (Mex1,= 61.60 vs Meont = 55.70). 2) students in experilllell tal group obtaiued higher rneall scores than cOlltrol group students iu overall technology competency (M exp=209.4 vs Mcont=175.28) a lld its compollents sucb as technology kllowledge (M exp=16.34 vs Meont= 15.81), technology skills (M exp=56 .34 vs Meont=41.10), and attit ude toward technology (M e:cp= 138.6 vs Meont= 1l8.02). 3) learning performance mean score of students in experimental group was higher than that of the control group (M e:cp= 15.78 vs Meont= 15.42) . For jufereutial al.lalysis tile statistical tests employed were the mixed between-within snbjects ANOVA, independent sample t-test, two-way ANCOVA, and two-way ANOVA. The following results were indicated: 1) experimental gronp performed significantly better than control group in terms of their overall level of self-directed leaming readiness (F (2, 152) = 27.42, p < . 001), self-management (F(2,152)= 14.80, p< .OOl) , desire for leaming (F(2,152)= 12.86, p< .OOl), and self-cont rol (F(2,152) = 12.86, p< .OOl). 2) Experimental group significant ly gained better than cont rol group regarding their overall level of technology competencies (F(2,152)= 49.25, p< .OOl ), technology skills,(F(2,152)= .46.76, p< .OO1), and attitude toward technology (F(2 ,152)= 24.84, p< .OOl ) . In terms of technology knowledge, however, there was no significant difference between the two groups (F(2,152) = 2.60, p> .05). 3) there was no significant difference between the experimental group and the cont rol gronp in terms of their leaming performance (t (76)= .945, p> .05). Additionally, it was observed that low achiever stndents obtained higher mean scores ill PoBL strategy, whereas high achiever stndellts fared bcttcr only when exposed to convcntional teaching strategy. mid achiever students,howevcr turned out to perform eq ually with both teaching strategies. Finally, it can be reasonably argued that since PoBL strategy proved to improve students' sclf-d irected learning readiness, technology competency, and learuing performance, t his strategy could be fairly integrated into the Iranian ET curriculum.